2014
DOI: 10.1186/1478-4491-12-33
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting motivation and retention of primary health care workers in three disparate regions in Kenya

Abstract: BackgroundThe World Health Organization (WHO) and the Government of Kenya alike identify a well-performing health workforce as key to attaining better health. Nevertheless, the motivation and retention of health care workers (HCWs) persist as challenges. This study investigated factors influencing motivation and retention of HCWs at primary health care facilities in three different settings in Kenya - the remote area of Turkana, the relatively accessible region of Machakos, and the disadvantaged informal urban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
135
1
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(157 citation statements)
references
References 21 publications
(34 reference statements)
13
135
1
8
Order By: Relevance
“…Findings show a number of contradictory views and perceptions among the three categories of HPs. Perceptions of life in rural areas are negative, even among rural-based health professionals, often associated with environmental factors such as schools, housing and safety being perceived as inferior in rural areas which is corroborated by previous findings Dolea et al (2010) and Ojakaa et al (2014). In addition, the quality of health care in rural areas was considered as poor by …”
Section: Discussionsupporting
confidence: 76%
“…Findings show a number of contradictory views and perceptions among the three categories of HPs. Perceptions of life in rural areas are negative, even among rural-based health professionals, often associated with environmental factors such as schools, housing and safety being perceived as inferior in rural areas which is corroborated by previous findings Dolea et al (2010) and Ojakaa et al (2014). In addition, the quality of health care in rural areas was considered as poor by …”
Section: Discussionsupporting
confidence: 76%
“…However, these findings are contrary to the country's estimates that allude that the female gender is more dominant in the health sector in Kenya (Kalibala, et al, 2005). With regard to HWs' level of training, the findings were similar to those made in Machakos, Nairobi and Turkana where it was observed that most HWs were holding diploma-level or higher education at 55.8%, 52% and 48.2% respectively (Ojakaa, et al, 2014). Nurses comprised the largest cadre 84 (35.4%), similar to the assertion that registered nurses formed the majority of health care workers at 28.7% (African Medical and Research Foundation (AMREF), 2012).…”
Section: Discussionsupporting
confidence: 72%
“…In unreliable work environments the culture is one of frustration, where staff do not consistently have the direction, support, or materials they need to do their jobs well or their work is not valued. 28,29 In creating a reliable work environment, the PPP system makes use of clearly outlined expectations (e.g., standard operating procedures, hospital targets and standards) and processes that lead to increased staff competency and accountability (e.g. training, performance metrics and incentives, disciplinary process), empowerment of management (e.g., managers can request additional hires and can discipline staff), formal and informal channels of communication (e.g., monthly reports, standing meetings, patient satisfaction surveys), and improved security and other support services (e.g., building and equipment maintenance, foodservice).…”
Section: Discussionmentioning
confidence: 97%